Comparison of Abuse Potentials of Teacher Candidates - Temel, Zeynep Fulya; Kurtulmuş, Zeynep; TORAN, MEHMET (My University, 2010)
Protection of children and children's rights which are associated with the welfare of a society is among the most critical problems of today in the world. Abuser people are not always the antisocial people, sometimes they may be the persons close to the child. Child abuse and neglect may be experienced in the family, among the peers, as well as in the educational environment. Abuser people are often the persons recognized by the child, the adults taking place in the immediate surroundings such as home, school, and office. Children are abused by the parents at home, and by the teachers, managers and employees at school environment. At school, reasons such as teacher's personality disorder, crowded classes, social pressures, adoption of beating as a discipline method cause abuse. The role and importance of the teachers is as great as the family's in raising the child. The children spend most of their time at school and with their teachers after their families and grow by mostly looking up to them as a model. This research examined whether there is any difference between the senior year students of Child Development Education and Preschool Education programs at Gazi University Faculty of Vocational Education, as well as of Elementary Education and Social Sciences programs at Faculty of Education regarding abuse potential. The research also examined whether there are significant differences regarding gender, age, monthly income, whether receiving treatment or not, and use of medication, number of members and number of working persons in the family, and unfavorable events experienced at school in regard to the abuse potentials of senior year students. A Demographic Information Form and Milner's Child Abuse Potential Scale was applied to the senior year students so as to collect their findings in the research. © Common Ground, Z. Fulya Temel, Zeynep Kurtulmus, Mehmet Toran.